Emergence of a 'new public sphere' in Bangladesh: the interactive dynamics between news television, citizens and the state. Issue 1 (1st January 2020) - Roy, Ratan Kumar
Abstract : The consideration of media as the watchdog of democracy is prolific in the context of Bangladesh. The emergence of private satellite television with its potential to broadcast news enables discursive space within the contested politico-social setup. The visibility aspect, variations and liveliness of news bulletins brought by the private television channels created an appeal among the viewers signifying the mediated culture. An attempt to examine the interactive dynamic between the media, public and politics offers new ground for exploring the communication and culture. This paper examines the control and contestation of domestic private televisions by unravelling the interface with audiences and the state. It shows an enmeshed trajectory of politics and rise of television news-making culture that provides new aspects to understand the relation between media and democracy. Further, it argues for an emergence of localised public sphere by underscoring the engagement of audiences with television news. It locates the new, mediated public sphere beyond the television set, in the locations where multiple actions of viewing, interacting and interpreting enable a discursive space which is politically active and meaningful.